PERSEPSI PENGGUNA TERHADAP PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM PENGAMBILAN KEPUTUSAN BISNIS PADA UMKM DI KOTA SAMARINDA - Sindi Aulia; Wira Bharata (BORJUIS: JURNAL OF ECONOMY, 2026)
The development of digital technology, particularly Artificial Intelligence (AI), has driven transformation in the micro, small, and medium enterprise (MSME) sector, particularly in supporting more effective, data-driven business decision-making. This study aims to analyze user perceptions of the use of AI in business decision-making among MSMEs in Samarinda City. The method used was a qualitative approach, with data collection through in-depth interviews with three MSME informants selected using purposive sampling. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that MSMEs' perceptions of AI tend to be positive, although levels of understanding vary. AI is considered beneficial in increasing efficiency, marketing effectiveness, and decision- making accuracy. However, several barriers exist, such as limited digital literacy, cost, and lack of technical understanding, requiring support to optimize its utilization.